Cáncer de pulmón no microcítico: quimioterapia y otros tratamientos sistémicos - Rodríguez-lajusticia, Laura; Villalobos, María Laura; García-paredes, Beatriz; Puente Vázquez, Javier; López-tarruella, Sara; Pérez Segura, Pedro; Díaz-rubio, Eduardo (Psicooncología, 2006)
Lung cancer is the most frequent neoplasia in industrialized countries and the leading cause of cancer death worldwide. Non-small cell lung cancer (NSCLC) accounts for 75-80% of lung carcinomas. Approximately one-third of these patients are diagnosed of locally advanced disease (Stage III of TNM staging system). Although surgery is the optimal treatment strategy, even in patients with stage I disease, approximately one third of them will die within 5 years, due to relapses and distant metastases. Several studies have explored the impact of neo-adyuvant chemotherapy in free disease survival and overall survival and adjuvant chemotherapy trials have been conducted to eliminate occult micrometastases and improve overall survival. In advanced disease, primary goals of therapy are palliation of symptoms as well as improvements in quality of life without high treatment-related toxicity.